2013
DOI: 10.1590/s1517-83822013000300032
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Group B Streptococcus serotypes III and V in pregnant women of Rio de Janeiro, Brazil

Abstract: GBS serotypes III and V were the most prevalent in pregnant women and exhibited resistance to tetracycline, clindamycin and sulfamethoxazole/trimethoprim. Serotype III showed high sialic acid content and PFGE analysis discerned 33 heterogeneous profiles. Phenotypic and genotypic characterization could be relevant to control GBS infections unaffected by intra-partum chemoprophylaxis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 18 publications
2
18
0
1
Order By: Relevance
“…PFGE is considered to be the golden standard of molecular typing methods and can determine clonal relationships between strains and indicate genetic origins or clonal diffusion [28,29]. In our study, PFGE showed that 63 GBS isolates were in 13 different pulsotypes; 10 isolates in PT4 and 6 isolates in PT6 had similar genotypes.…”
Section: Discussionmentioning
confidence: 51%
“…PFGE is considered to be the golden standard of molecular typing methods and can determine clonal relationships between strains and indicate genetic origins or clonal diffusion [28,29]. In our study, PFGE showed that 63 GBS isolates were in 13 different pulsotypes; 10 isolates in PT4 and 6 isolates in PT6 had similar genotypes.…”
Section: Discussionmentioning
confidence: 51%
“…(27) Rates of resistance ranging from 0% to 14.3% and 7.7% to 12.2% for erythromycin and clindamycin, respectively were detected in studies performed in GBS isolated from pregnant women in Rio de Janeiro, Brazil. (32,33) In contrast, high rates of resistance for both antimicrobials were detected in other Brazilian studies (Table 3).…”
Section: Resultsmentioning
confidence: 67%
“…12 GBS serotyping is conventionally performed by the latex agglutination method, with a high rate of untypable strains or erroneous classifications. 3,11,13,14 In this context, the use of more sensitive and specific methods of GBS identification, such as molecular approaches based on the amplification of the nucleotide sequences of genes responsible for the expression of GBS capsular components, allow the recognition of strains not detected by conventional methods. 10,11 Among these molecular methods, multiplex PCR, which permits the detection of the ten GBS serotypes in a single reaction, is particularly amenable to routine laboratory use because of its ease of implementation, low cost and increased reliability compared to conventional serotyping.…”
Section: ■ Resultsmentioning
confidence: 99%